2021
DOI: 10.1002/ajmg.c.31951
|View full text |Cite
|
Sign up to set email alerts
|

Dysautonomia in the Ehlers–Danlos syndromes and hypermobility spectrum disorders—With a focus on the postural tachycardia syndrome

Abstract: Dysautonomia (autonomic dysfunction) occurs in the Ehlers-Danlos syndromes (EDS) and hypermobility spectrum disorders (HSD). Symptoms include palpitations, dizziness, presyncope, and syncope, especially when standing upright. Symptoms of orthostatic intolerance are usually relieved by sitting or lying and may be exacerbated by stimuli in daily life that cause vasodilatation, such as food ingestion, exertion, and heat. Neurocardiovascular dysautonomia may result in postural tachycardia syndrome (PoTS), a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 67 publications
2
8
0
1
Order By: Relevance
“…Regarding other comorbidities such as chronic fatigue, dysautonomia (e.g., orthostatic intolerance, POTS), psychological distress (e.g., anxiety, sleep disturbances, impaired memory/concentration, depression), functional gastrointestinal and bladder disorders, and allergic/atopic features, we found that, with a few exceptions, the presence of individual comorbid features was no more or less frequent in hEDS and HSD, in line with other reports (Brock et al, 2021; Celletti et al, 2020; Hakim et al, 2021; Lam et al, 2021; Mathias et al, 2021; McGillis et al, 2020; Ruiz Maya et al, 2021; Wasim et al, 2019). In addition, many of these comorbidities are also frequently observed in other EDS forms, such as classical and vascular EDS, as well as rarer types (Malfait et al, 2020; Ritelli, Rovati, et al, 2020; Ritelli, Venturini, et al, 2020), and in other chronic pain and fatigue conditions (Hakim et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding other comorbidities such as chronic fatigue, dysautonomia (e.g., orthostatic intolerance, POTS), psychological distress (e.g., anxiety, sleep disturbances, impaired memory/concentration, depression), functional gastrointestinal and bladder disorders, and allergic/atopic features, we found that, with a few exceptions, the presence of individual comorbid features was no more or less frequent in hEDS and HSD, in line with other reports (Brock et al, 2021; Celletti et al, 2020; Hakim et al, 2021; Lam et al, 2021; Mathias et al, 2021; McGillis et al, 2020; Ruiz Maya et al, 2021; Wasim et al, 2019). In addition, many of these comorbidities are also frequently observed in other EDS forms, such as classical and vascular EDS, as well as rarer types (Malfait et al, 2020; Ritelli, Rovati, et al, 2020; Ritelli, Venturini, et al, 2020), and in other chronic pain and fatigue conditions (Hakim et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Dysautonomia is also common and can impact pain and fatigue levels. Autonomic dysfunction may underlie both musculoskeletal pain and fatigue (Mathias et al, 2021; Ruiz Maya et al, 2021). Psychiatric and psychological comorbidities like depression and anxiety also frequently co‐occur and can worsen physical symptoms (Baeza‐Velasco et al, 2021; Bulbena‐Cabré et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was based on experience over three decades and on information in the two autonomic departments that he developed and directed (at St Mary's Hospital/Imperial College London and the Autonomic Unit at Queen Square, University College London). Pre-pandemic evaluation utilised ambulatory and programmed BP/HR recorders (as used in hypertension assessment), with additional measurements while lying and standing, and to food and physical exertion [13,14]. This became challenging during the pandemic as the patients needed to travel to the centre to collect the recorders and there was uncertainty about equipment sterilising procedures to avoid virus transmission.…”
Section: Methodsmentioning
confidence: 99%
“…The targets of the autonomic nervous system include body temperature, heart rate, respiration, bowel movements and digestion, sexual arousal, endocrine function, blood pressure regulation and vascular tone. However, when the autonomic nervous system malfunctions, it can lead to symptoms and diseases of dysautonomia, affecting many different functions of the autonomic nervous system including vascular tone and blood pressure as seen with Raynaud’s syndrome (RS) 1 .…”
Section: Mainmentioning
confidence: 99%